Fruit industry of Kansas - Allison, Thomas Walter (My University, 1898)
Introduction: The treatment of a subject of this kind in an essay of fifteen hundred or two thousand words must of necessity take up but few phases and give but little of what might be written on each phase. The aim is to show as clearly as possible the resources of Kansas as a fruit growing state, the position of Horticulture among the industries, and its position horticulturally among the states; to give a short history of the growth of the fruit industry in the state, and to discuss, to limited extent, the various kinds of fruits produced, the varieties best suited to the state, and the cultivation, protection, packing, and marketing of our fruits.
Citation: Allison, Thomas Walter. Fruit industry of Kansas. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Kansas; Fruit Industry; Horticulture; Cultivation; Theses; Manuscripts (documents)